Driver drowsiness detection system with opencv and keras. Issue 1 (May 2021) - Vishnu, R.; Vishvaragul, S.; Srihari, P.; Nithiavathy, R.; Asmitha shree, R.
Abstract: Drowsiness of the drivers is the principal cause of injuries in the world. Because of loss of sleep and tiredness, drowsiness can occur even as riding. The first-rate manner to keep away from accidents because of drivers' drowsiness is to come across drowsiness of the driving force and warn him before fall into sleep. To discover drowsiness many techniques like eye retina detection, facial function recognition has been used. Here on this paper, we suggest a way of detecting motive force drowsiness, the usage of eye retina detection and pulse charge detection of the driving force. On this record, we endorse an extra accurate drowsiness detection approach which is a hybrid technique of eye retina detection and pulse sample detection.